What I Learned in My Great American Newsroom Trip. - CUMMINGS, MEREDITH (Quill)
The author discusses his cross-country trip, dubbed #followmyled, on social media to chronicle journalism in the U.S. in 2017. Topics mentioned include the author's visit of several news outlets wherein he found that what the people says about the media does not sync with his experience as a journalist, his study of watching creative people work as he documented the reality of American newsrooms, and the struggle of local journalists on the consequences of the reputation of national media.